A Panel of Cultures of Cancer and Normal Lung Cells with a Characterized Expression of PD-L1 to Search and Development of the Target Modifiers of Immunotherapy - T. A. Bogush; A. N. Grishanina; A. M. Scherbakov; D. A. Khochenkov; R. Yu. Yunusova; S. A. Kalyuzhny; V. S. Kosorukov (Антибиотики и Химиотерапия)
Background. The search for eﬀective combinations of immune checkpoint inhibitors with common cytostatics, targeted cancer drugs and other treatments is a modern trend to improve the eﬀectiveness of immunotherapy.Purpose. Development of a panel of lung cancer cell cultures and cells of normal lung tissue with a characterized molecular phenotype by expression of one of the targets of immunotherapy — programmed cell death ligand 1 (PD-L1).Methods. PD-L1 expression was quantitatively analyzed by immunoﬂuorescence method associated with ﬂow cytometry.Results. A panel of lung cancer cell cultures of diﬀerent histotypes and cells of normal lung tissue with characterized molecular phenotype was formed according to the expression of the immunotherapy target PD-L1. In terms of PD-L1 expression intensity, cell cultures can be arranged in a series: Calu-1  HFL-1  Calu-6  Wi-26  A-549  H-596  H-211, with a 7-fold diﬀerence in the index between Calu-1 and H-211.Conclusion. The panel of cultures of cancer and normal lung cells is recommended for the search and development of eﬀective modiﬁers of the immunotherapy target PD-L1.